Femoral neck fracture patients with ischaemic stroke choose hemiarthroplasty or constrained liner total hip arthroplasty? A retrospective comparative study of 199 cases - Huo, Jia; Liu, Sikai; Li, Mengnan; Liu, Zeming; Ding, Xuzhuang; Liu, Bo; Li, Huijie; Han, Yongtai (Frontiers in Surgery, 2023)
The objective of this study was to assess the long-term survival rate, complications, as well as the clinical and radiological outcomes of hemiarthroplasty and total hip arthroplasty using constrained polyethylene liners in patients with ischemic stroke.This study was a retrospective cohort study that included patients with ischemic stroke who underwent hip arthroplasty from March 2010 to September 2017. In the Constrained Acetabular Liners (CAL) group, patients received an uncemented acetabular shell with a constrained polyethylene liner. The Dual Mobility (DM) group underwent hemiarthroplasty (HA). Additionally, hip function, range of motion, quality of life, the incidence of clinical complications, and prosthesis stability were investigated.Results 96 patients with unilateral femoral neck fractures who underwent hip replacement with CAL were included in the CAL group, while 103 patients who underwent hip replacement with a dual mobility head 2 were included in the DM group. VAS, and SF-36 data were available for both CAL and DM groups. At the 1-year postoperative follow-up, the HHS in the CAL group was significantly lower than that in the DM group (80.83±3.91 vs. 83.17 ± 4.15, P < 0.05). The VAS score in the CAL group peaked at the 1-year follow-up (2.07 ± 0.91 vs. 1.49 ± 0.85, P < 0.05). However, there were no significant differences between the two groups in terms of HSS, VAS, and SF-36 at the last follow-up after surgery. Operative time and the amount of bleeding in the DM group were significantly lower than those in the CAL group (105.30 ± 29.68 vs. 94.85 ± 31.07; 355.11 ± 123.95 vs. 302.22 ± 107.68, P < 0.05). Additionally, there was no significant difference in the mean leg length discrepancy between the two groups.The clinical, imaging, and postoperative complications of the CAL and DM groups were analyzed. The prognosis for DM appears to be more beneficial for early patient recovery, but a higher likelihood of recurrent dislocation is observed. CAL offers excellent stability for primary THA in high-risk patients; however, attention should be given to preventing aseptic loosening.